2019
DOI: 10.1002/cmdc.201900018
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship Studies of the Natural Product Gq/11 Protein Inhibitor YM‐254890

Abstract: G proteins act as molecular switches in G protein‐coupled receptor signaling pathways and are key mediators for numerous important physiological processes. The natural product, cyclic depsipeptide YM‐254890, together with the structurally similar FR900359, is the only known selective inhibitor of the Gq/11 subfamily of G proteins. We recently reported the first total synthesis of YM‐254890 and FR900359, followed by synthesizing analogues to perform structure–activity relationship studies. However, incomplete i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 27 publications
(60 reference statements)
1
30
0
Order By: Relevance
“…The inhibitory effect on G q ‐, G s ‐ and G i ‐mediated signaling of YM‐254890 and analogs has been characterized by inositol monophosphate (IP 1 ) assay of the M 1 muscarinic receptor in Chinese hamster ovary (CHO) (G q signaling), isoproterenol‐induced cAMP assay of the β 2 ‐adrenergic receptor in human embryonic kidney (HEK) 293 cells (G s signaling), and cAMP assay of the rat metabotropic glutamate receptor 2 (mGlu 2 receptor) in CHO cells (G i signaling). Here it was shown that YM‐254890 is a potent, selective inhibitor of G q ‐mediated signaling (Figure A), verifying the important pharmacological role of N ‐MeDha residue in YM‐254890 for strong inhibition of G q ‐mediated signaling, as analogs 9 to 15 , which replaced the N ‐MeDha residue with residues with d ‐stereochemistry and variations in the side chains, and the hydrogenated analogs, analogs 7 and 8 also generated by hydrogenation of N ‐MeDha in the natural product to epimeric N ‐Me‐ l ‐Ala and N ‐Me‐ d ‐Ala, respectively, are all less potent than YM‐254890 (Figure ). It was also outlined that the structural integrity of YM‐254890 is critical for possessing potent G q inhibition activity, as even small structural changes can result in substantial differences in pharmacological activity, however, modification at certain sites were allowed and did not compromise potency (Figures a and ).…”
Section: Selective Gq Inhibitorsmentioning
confidence: 54%
See 4 more Smart Citations
“…The inhibitory effect on G q ‐, G s ‐ and G i ‐mediated signaling of YM‐254890 and analogs has been characterized by inositol monophosphate (IP 1 ) assay of the M 1 muscarinic receptor in Chinese hamster ovary (CHO) (G q signaling), isoproterenol‐induced cAMP assay of the β 2 ‐adrenergic receptor in human embryonic kidney (HEK) 293 cells (G s signaling), and cAMP assay of the rat metabotropic glutamate receptor 2 (mGlu 2 receptor) in CHO cells (G i signaling). Here it was shown that YM‐254890 is a potent, selective inhibitor of G q ‐mediated signaling (Figure A), verifying the important pharmacological role of N ‐MeDha residue in YM‐254890 for strong inhibition of G q ‐mediated signaling, as analogs 9 to 15 , which replaced the N ‐MeDha residue with residues with d ‐stereochemistry and variations in the side chains, and the hydrogenated analogs, analogs 7 and 8 also generated by hydrogenation of N ‐MeDha in the natural product to epimeric N ‐Me‐ l ‐Ala and N ‐Me‐ d ‐Ala, respectively, are all less potent than YM‐254890 (Figure ). It was also outlined that the structural integrity of YM‐254890 is critical for possessing potent G q inhibition activity, as even small structural changes can result in substantial differences in pharmacological activity, however, modification at certain sites were allowed and did not compromise potency (Figures a and ).…”
Section: Selective Gq Inhibitorsmentioning
confidence: 54%
“…Analog 57 was generated by hydrogenation of the N ‐MeDha in FR900359 to a mixture of N ‐Me‐ l ‐Ala and N ‐Me‐ d ‐Ala, and slightly less potent than FR900359 (Figure ), indicating the α,β‐unsaturated exomethylene group within FR900359 is not crucial for Gα q/11 inhibition. However, prior published data suggest that the unsaturated exomethylene group in YM‐254890 plays an important role in the inhibition of G q ‐mediated signaling (Figure ) . This conflicting result may have been a result of the different cell‐assays conditions or from using the two slightly different structural templates.…”
Section: Selective Gq Inhibitorsmentioning
confidence: 98%
See 3 more Smart Citations